ECONOMIC GROWTH TESTED BY TAX ARRANGEMENTS : AN ISSUE OF READABILITY FOR COMPANIES IN MOROCCO - EL HARMOUZI , Nouh; SENTISSI , Ouiam (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Economic growth is a major issue for a country such as Morocco, that is in the pursuit of a growth born from the added values created by the companies and not only the State. The tax structure is undergoing a gradual change that breaks away from the aims of the tax reform of the 80’s at this stage. The current context in Morocco is marked by two interesting social and economic phénoména : firstly, a revolution of households and sectors perceiving a tax pressure that is expanding continuously, and also the need to digitize billing to tackle informality. Secondly, a major evolution in taxation is noted, which is unreadable and understandable especially that the strengthening of tax control is the key that will enable the state to boost the coffers of public treasury. The purpose of this study is to assess the impact of fiscal policy on the country’s economic development.